Inclusion is a feeling, not a place: a qualitative study exploring autistic young people's conceptualisations of inclusion. Issue 12 (14th October 2020) - Goodall, Craig
ABSTRACT: This study investigates from their perspectives, the educational experiences of twelve autistic young people (aged 11–17 years) for whom mainstream was, or is, challenging. This paper focuses on one theme from this study and presents how these young people experience, define and conceptualise inclusion. A flexible qualitative participatory approach was used incorporating a range of methods, including: one-to-one semi-structured interviews; draw and write activities; a beans and pots activity; and, diamond ranking activities. These methods, and the topics discussed, were developed by an advisory group of three young people. Outcomes of this study suggest that mainstream school is not suitable for all autistic young people. Inclusion, for them, is not synonymous with mainstream and can occur in any school. They defined inclusion as belonging, being valued and wanted as a person by teachers, of fairness and of being afforded the necessary support to access and thrive in education. In short, inclusion is a feeling (a sense of belonging), not a place (mainstream or otherwise).